Transient Thermal Stress in Bimodulus Sphere with Orthotropic Temperature-Dependent Properties - Kamiya, N. (Engineering Transactions, 1980)
Transient thermal stress problems for a bimodulus elastic material are analysed in this paper. Temperature-dependent mechanical and thermal properties of the material are considered. Fundamental governing equations for an orthotropic spherically symmetric bimodulus model are derived. Numerical illustrations of transient thermal stresses in a hollow sphere are presented.